CWNA : Certified Wireless Network Administrator Official Study Guide (Exam PW0-100) - Carpenter, Tom, 1972-; Series Editors Barrett, Joel (New York McGraw-Hill, 2008)
A guide to CWNA exam. It covers exam objectives for network professionals and wireless LAN engineers seeking to become certified wireless network administrators. It features step-by-step exercises and self-tests in every chapter. It contains more than 150 practice questions
Include Index
Keywords: Electronic data processing personnel--Certification -- Telecommunications engineers--Certification